Pembuatan Background Dengan Skema Monokromatik Untuk Membangun Suasana Dramatis Pada Film “Contrast: Two Sided Life” - Nidha, Fatma Qutrotun; Yulianti, Ika; Warman, Rahmat Aditya (Institut Seni Indonesia Yogyakarta, 2025)
To create a successful animation that is popular with the public, it is necessary to pay attention to various aspects, one of which is the creation of a background. The background helps build the story and atmosphere in an animated film. This study discusses the creation of a visual background with a monochromatic scheme to build a dramatic atmosphere in the animated film